2015
DOI: 10.3382/ps/pev058
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C prevents the effects of high rearing temperatures on the quality of broiler thigh meat

Abstract: We investigated the effects of incubation temperatures and vitamin C injections into eggs (treatments: 37.5ºC, 39ºC, 39ºC+vitamin C) on resultant chick pectoralis major and sartorius muscle fiber hypertrophy, as well as their effects on the quality of breast and over-thigh meat of broilers reared under cold, control, or hot temperatures. Incubation at 39ºC increased the shear force and reduced meat redness in breast meat (P < 0.05). Vitamin C prevented these high temperature incubation effects [shear force (kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Egg water loss depends of eggshell porosity , given by its pore number, diameter, length, and shape. Therefore, it is higher in eggs laid older breeders or larger eggs from a same breeder age incubated at high temperatures and/or low relative humidity levels (Morita et al, 2009(Morita et al, , 2010Sgavioli et al, 2015). Although the velocity of the air on the egg surface has no direct effect on water loss (Meijerhof & van Beek, 1993), as previously mentioned in this review, it allows continuous conductive-convective heat dissipation, and therefore, indirectly influences egg water loss.…”
Section: Egg Water Transfermentioning
confidence: 81%
See 4 more Smart Citations
“…Egg water loss depends of eggshell porosity , given by its pore number, diameter, length, and shape. Therefore, it is higher in eggs laid older breeders or larger eggs from a same breeder age incubated at high temperatures and/or low relative humidity levels (Morita et al, 2009(Morita et al, , 2010Sgavioli et al, 2015). Although the velocity of the air on the egg surface has no direct effect on water loss (Meijerhof & van Beek, 1993), as previously mentioned in this review, it allows continuous conductive-convective heat dissipation, and therefore, indirectly influences egg water loss.…”
Section: Egg Water Transfermentioning
confidence: 81%
“…It was demonstrated that eggshell temperature increases from the second third of incubation at 36-39°C incubation temperature (Sgavioli et al, 2015;Almeida et al, 2016;. This increase is related with the greater metabolic heat production by the fetus during this high growth rate phase (Lourens et al, , 2007.…”
Section: Eggshell Temperaturementioning
confidence: 93%
See 3 more Smart Citations